On the Psychology of Military Incompetence - Dixon, Norman (London Jonathan Cape, 1976)
MILITARY HISTORY. The Crimea, the Boer War, the Somme, Tobruk, Pearl Harbor, the Bay of Pigs: these are just some of the milestones in a century of military incompetence, of costly mishaps and tragic blunders. Are these simple accidents-as the "bloody fool" theory has it-or are they inevitable? The psychologist Norman F. Dixon argues that there is a pattern to inept generalship, and locates this pattern within the very act of creating armies in the first place, which in his view produces a levelling down of human capability that encourages the mediocre and limits the gifted. In this light, successful generals achieve what they do despite the stultifying features of the organization to which they belong. A classic study of military leadership, On the Psychology of Military Incompetence is at once an original exploration of the battles that have defined the last two centuries of human civilization and an essential guide for the next generation of military leaders.
Include Index
Keywords: Militarism -- Military history -- Generals--Psychology